2023
DOI: 10.1080/02670836.2022.2152927
|View full text |Cite
|
Sign up to set email alerts
|

Fretting wear behaviour of ultrafine-grained copper produced by cryogenic temperature extrusion machining

Abstract: Cryogenic temperature extrusion machining (CT-EM), as a new process, was first applied for preparing ultrafine-grained (UFG) copper strips. The microstructure evolution and mechanical properties (hardness and fretting wear) were characterised by electron backscatter diffraction and transmission electron microscopy methods. Refined grains (450 nm) and high dislocation density could be obtained by CT-EM because of effectively suppressing heat generation and the annihilation of dislocations. As a result, the CT-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Moreover, it can also be observed that the MoSiBTi alloys experience severe plastic deformation, and the worn surface shows large and continuous plowing grooves along the sliding direction, which is a typical characteristic produced by two-body abrasion wear. This is because the Al 2 O 3 ceramic has a much higher hardness than the MoSiBTi alloys; once the hard abrasive particles intrude into the ductile metal matrix, severe plastic deformation and plowing are inevitable [33]. The decreased hardness and strength of MoSiBTi alloys leads to more severe plastic deformation and plowing on the wear tracks, and thus results in an increased wear loss.…”
Section: Friction and Wear Behaviourmentioning
confidence: 99%
“…Moreover, it can also be observed that the MoSiBTi alloys experience severe plastic deformation, and the worn surface shows large and continuous plowing grooves along the sliding direction, which is a typical characteristic produced by two-body abrasion wear. This is because the Al 2 O 3 ceramic has a much higher hardness than the MoSiBTi alloys; once the hard abrasive particles intrude into the ductile metal matrix, severe plastic deformation and plowing are inevitable [33]. The decreased hardness and strength of MoSiBTi alloys leads to more severe plastic deformation and plowing on the wear tracks, and thus results in an increased wear loss.…”
Section: Friction and Wear Behaviourmentioning
confidence: 99%